Characterization of bitter vetch (Vicia ervilia (L.) Willd.) landraces conserved on-farm in Lemnos Island - Bebeli P.J.; Livanios I.; Lazaridi E. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Lemnos Island presents a rich biodiversity in legume genetic resources both in wild and cultivated species that provide ecological benefits and have high nutritious value as food and feed. Among the cultivated genetic material that is conserved on farms, landraces of a neglected fodder crop, bitter vetch, have evolved under harsh climatic conditions when grown under traditional farmer practices. Lemnian bitter vetch landraces, along with other populations collected on farms and landraces with Greek origin conserved ex situ were characterized using 24 agro-morphological traits and the phenotypic diversity among and within populations was estimated. The mean total phenotypic diversity of the whole collection was HT=0.52 while the mean phenotypic diversity among populations studied (GST) was 0.31. A significant variability was revealed among Lemnian populations regarding their morphological and agronomical traits. Applying Discriminant Analysis the three landraces from Lemnos were clustered in separate groups and differentiated from each other mainly due to their days to flowering, days to pod setting and their productivity. On-farm cultivated bitter vetch landraces of Lemnos consist therefore a variable genetic material and on farm management seems to be a valuable conservation practice in the case of this isolated island.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)